The advancement of wind farm projects in agrarian reform areas in Rio Grande do Norte - Bezerra, Jéssica Bittencourt; Lopes, João Marcos de Almeida; Bentes Sobrinha, Maria Dulce Picanço (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective - This article aims to discuss the expansion of wind power projects and their possible impacts on agrarian reform areas in the state of Rio Grande do Norte (RN), Brazil. The research is based on the observation that social struggle enabled the occupation of part of the semi-arid region of the state through rural settlements, whose dynamics have been changing due to the installation of wind farms—generating new territorial paradigms marked by conflicts and reconfigurations of everyday life. Methodology - The study is based on a literature review on the territorialization of wind energy, analysis of data from the Brazilian Electricity Regulatory Agency (ANEEL, 2024), and fieldwork carried out at the Maria da Paz settlement, located in the municipality of João Câmara (RN). The qualitative approach integrates document analysis, on-site observations, and interviews with settlers, seeking to understand the socio-spatial transformations triggered by the arrival of energy companies. Originality/relevance - The article contributes to the critical debate on the relationship between energy transition and territorial justice by addressing a topic still underexplored: the effects of renewable energy expansion on agrarian reform territories. The analysis reveals the tension between sustainability discourses and the processes of capital (re)territorialization, exposing institutional weaknesses in protecting settled communities. Results - It was found that, although wind farms are not predominantly located within the settlements, their interferences are significant. The impacts include landscape changes, socio-environmental conflicts, the weakening of community relations, and limited mitigation measures. Settlers report symbolic losses, production difficulties, and a lack of effective dialogue with the companies. Theoretical/methodological contributions - The study provides theoretical support for a critical analysis of contemporary processes of territorial appropriation by energy capital agents. Methodologically, it stands out for its articulation between official data, active listening to rural subjects, and a situated analysis of conflicts, contributing to studies on agrarian reform, energy, and territorial conflict. Social and environmental contributions - The findings reinforce the importance of public policies that integrate agrarian reform and energy transition with social justice. The article proposes a reflection on the need for institutional mechanisms to ensure community protagonism in decision-making processes, the protection of their ways of life, and the construction of more inclusive and territorially just energy alternatives.